2005
DOI: 10.1029/2004je002295
|View full text |Cite
|
Sign up to set email alerts
|

On lateral mixing efficiency of lunar regolith

Abstract: [1] To reexamine the potential for lateral mixing over large distances (>100 km) by impact craters, a mathematical model utilizing the stable probability distribution is proposed for estimating lateral mixing efficiency on the Moon. The proposed model divides material mixing into shallow slope and steep slope regimes. Mixing in the shallow slope regime conforms to the condition that the exponent of the power law describing lunar crater size frequency is larger than the exponent of the power law describing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…For example, the Apollo 15 lunar module site was in the secondary field (South Cluster) of rays of either Autolycus or Aristarchus Crater [ Swann et al , ]. Li and Mustard [] suggest that distal ejecta from distances of >100 km away could explain an elevated amount of nonlocal material in a sampling location, though, again, they did not consider the heterogeneous nature of this distal ejecta.…”
Section: Two Sets Of Contradictory Observational Constraints On Matermentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the Apollo 15 lunar module site was in the secondary field (South Cluster) of rays of either Autolycus or Aristarchus Crater [ Swann et al , ]. Li and Mustard [] suggest that distal ejecta from distances of >100 km away could explain an elevated amount of nonlocal material in a sampling location, though, again, they did not consider the heterogeneous nature of this distal ejecta.…”
Section: Two Sets Of Contradictory Observational Constraints On Matermentioning
confidence: 99%
“…Li and Mustard [] suggested that large craters >100 km away from contacts may explain the elevated nonmare abundance of >20% in most mare soil samples. To test this large crater hypothesis, we performed a global run to account for the effect of larger craters at large distances from the mare/highland contact.…”
Section: Implications Of Our Impact Transport Model For Evolution Of mentioning
confidence: 99%
See 2 more Smart Citations
“…The formalism does not, however, give a value of the ejecta thickness at a particular point—only the characteristic function of the probability density function (pdf) of the total ejecta thickness, φ ρ ( u ): φρ(u)=expλ|u|αρ[1i0.3emsgn0.3em(u)tan0.3em(πα/2)], λ=πγR0αρF2αρk(γ22h/k)(2ρ)αρk2normalΓ(1αρ)cos(παρ/2), αρ=γ/(k+h), where Γ is the Gamma function, i=1, and sgn( u ) is 1 if u > 0 and −1 if u < 0. Obtaining the pdf from this characteristic function requires the use of a numerical integrator, and we follow Li and Mustard [] in using the STABLE code [ Nolan , ].…”
Section: Implications For the Origin Of The Th Distributionmentioning
confidence: 99%